2020
DOI: 10.3389/fvets.2020.00242
|View full text |Cite
|
Sign up to set email alerts
|

Craniomaxillofacial Trauma in Dogs—Part II: Association Between Fracture Location, Morphology and Etiology

Abstract: Treatment of craniomaxillofacial (CMF) trauma in dogs requires a thorough understanding of the CMF skeletal structures involved. The human medical literature has several examples of CMF trauma and fracture classification, including the classically described Le Fort fractures. The recent classification schemes require large studies using computed tomography (CT). In the veterinary medical literature, such studies are lacking. The aims of part II of this retrospective study were to use a large number of CT studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…The overarching goal of this and similar studies is to identify instances where MRI can be used in lieu of CT to provide adequate concurrent assessment of traumatic brain injuries and associated fractures of the cranial vault. Despite the good diagnostic performance of MRI in facial fracture assessment in this study, CT will likely remain the gold standard for imaging of animals with maxillofacial trauma, especially when planning surgical interventions (38,39). MRI had least agreement with CT in the detection of TMJ fractures.…”
Section: Discussionmentioning
confidence: 77%
“…The overarching goal of this and similar studies is to identify instances where MRI can be used in lieu of CT to provide adequate concurrent assessment of traumatic brain injuries and associated fractures of the cranial vault. Despite the good diagnostic performance of MRI in facial fracture assessment in this study, CT will likely remain the gold standard for imaging of animals with maxillofacial trauma, especially when planning surgical interventions (38,39). MRI had least agreement with CT in the detection of TMJ fractures.…”
Section: Discussionmentioning
confidence: 77%
“…The separation of the median palatine suture occurs frequently with fractures of the orbit, nasopharynx, and nasal bones ( 2 ). In the presence of maxillofacial/head trauma, a CT is recommended for full assessment of any fractures ( 2 , 4 , 10 ). The cats that had CT performed in this study presented with more severe clinical findings which explains the association found between CT imaging and the presence of more severe head injury, orbital or ocular injury, symphyseal separation, and placement of a feeding tube.…”
Section: Discussionmentioning
confidence: 99%
“…The hard palate is formed by the paired incisive, maxillary, and palatine bones that are fused together at the intermaxillary suture. The separation of the median palatine suture or fracture of the bones of the hard palate occurs frequently with multiple and bilateral fractures of the midface (incisive bone, maxilla and palatine bone, orbit, zygomatic arch, and nasopharynx) ( 2 , 4 ). Dental, ocular, and neurologic injuries also are common.…”
Section: Introductionmentioning
confidence: 99%
“…The best treatment, conservative or surgical, should be chosen after an attentive evaluation of the extension of the lesions. Computed tomography allows excellent visualization of bone defects, soft tissue damage, and the detection of the presence of foreign bodies and hematomas 1,17,18 . It also permits 3‐dimensional reconstructions that are useful for surgical planning 17,19 .…”
Section: Discussionmentioning
confidence: 99%